Perfil metabolômico do plasma seminal de touros guzerá (Bos taurus indicus) com diferentes parâmetros de congelabilidade do sêmen - Pessoa, Eduardo Rodrigues (2021)
Seminal plasma, in addition to being an important carrier medium for ejaculated sperm, is connected to several metabolites that play a significant role in many biological events and have been linked to possible biomarkers, helping to predict the reproductive potential of selected animals. The present study aimed to evaluate the seminal plasma metabolites of Bos taurus indicus bulls of the Guzerá breed and their associations with semen freezability. Semen from nine adult bulls was collected by electroejaculation, followed by andrological examination and cryopreservation. Afterwards, the semen was thawed and the seminal parameters were evaluated by CASA. Seminal plasma samples from bulls were prepared and then analyzed using gas chromatography combined with mass spectrometry (GC-MS) and multivariate and univariate analyzes. The seminal plasma metabolites and their respective pathways were identified by bioinformatics from Xcalibur and Cytoscape programs and the MetaboAnalyst platform. Sixty-two metabolites were identified in the seminal plasma of the bulls. 1,3-Dioxan-5-ol, stearic acid, cholesteryl myristate, 2-ethylheptanoic acid and isobutylamine were the most abundant metabolites, while heptadecanoic acid, pyrrolidine, nonadecanoic acid, 1-ethyl-1-nitrosourea and ethyl lactate were the least abundant metabolites in the seminal plasma. The multivariate statistical analysis indicated a distinct separation between high and low freezability bulls. The metabolites with the highest score of variable importance in the projection (VIP> 1.0) included propanoic acid, ribose, glycine, heptadecanoic acid and undecanoic acid. Among the compounds, propanoic acid (VIP = 3.5) and ribose (VIP = 2.3) were more abundant in the high freezability group (HF) than in the low freezability group (LF). The t-test analysis suggested that only the concentration of ribose was significant (P = 0.014). This metabolite can influence the reduction of oxidative stress, the repair of DNA damage and the prevention of cellular apoptosis, in addition to serving as a possible source of energy for the body. Thus, ribose can be considered a biomarker of seminal freezability in bulls. As far as it is known, this is the first study to conduct an evaluation of the metabolites in the seminal plasma of Guzerá bulls related to different freezability phenotypes. The findings of this study will serve to assist the development of new research and a better understanding of the mechanisms of sperm cryopreservation.